STABILITY OF THE DYNAMIC MODEL OF SVPR SEXUAL VIOLENCE CASES - Bahri, Susila; Riyandi, Hanif Rayhan; Rudianto, Budi (PATTIMURA UNIVERSITY, 2024)
In this study, the stability of the equilibrium points of the Susceptible Violent Punishment Recovered (SVPR) model in the spread of sexual violence cases is analyzed. The model assumes that sexual violence can spread similarly to the transmission of infectious diseases. The constructed model is a system of nonlinear differential equations. The model has two equilibrium points: the equilibrium point with sexual violence-free and the endemic equilibrium point with sexual violence. Stability analysis is then carried out for both fixed points, indicating that the violence-free equilibrium is asymptotically stable if the basic reproduction number . Meanwhile, the endemic equilibrium is asymptotically stable if the condition and four other conditions are satisfied. Numerical simulations are required to observe the implementation of the model using MAPLE software. As for this research, we conclude a model that shows the spread of sexual violence is not widespread because it was found that .